Information and communication technology (ICT) integration in teacher education institutions - Peralta, Shelanee Theresa P. (2007)
The expressed attitudes, perceived skill level, and level of ICT integration to instruction of teacher educators in state universities, autonomous and deregulated teacher education institutions were investigated in this study. The study was conducted on nine teacher education institutions in the National Capital Region. Questionnaires were used and the results revealed that generally, teacher educators have positive attitudes towards ICT integration and they consider themselves Good in the integration. The findings showed that the significant predictor of ICT integration is perceived skill level. This supports the recommendation of this study to strengthen pre-service and in-service trainings on ICT integration.
"October 2007."
Thesis (M.A. Educational Technology)--University of the Philippines, Diliman.
Keywords: Teachers -- Training of -- Philippines -- Manila Metropolitan Area; Information technology -- Philippines -- Manila Metropolitan Area; Educational technology -- Philippines -- Manila Metropolitan Area